Investigating Factors Underlying Boredom in Learning English: The Case of Secondary School - Achmad Kholili (Al-Lisan: Jurnal Bahasa, 2023)
Former studies have demonstrated that the success of language learning is influenced by several factors such as cognitive, affective, and social factors. Learners with high motivation in learning will surely influence their success in language learning. On the other hand, those who have a poor motivation to learn will result in poor academic achievement. One of the affective factors that have also affected learners’ progress in language learning is boredom in language learning. Drawing on the qualitative lens, the current study has attempted to investigate factors underlying this notion at the secondary school level. Six learners voluntarily participated in this study as the research participants. In the meantime, a written reflection (WR) and Focus-Group Discussion (FGD) were distributed to them so as to know such factors underlying their boredom in learning English. The findings indicated that factors underlying learners’ boredom in language learning include classroom factors, linguistic factors, teaching and learning factors, and environmental factors. These findings have given an empirical contribution to the school. Suggestions are also put forward at the end of this paper.